Factors that affect attitude towards agriculture among university students in Malaysia: the case of contract farming - Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Uli, Jegak; Abu Samah, Bahaman (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
Agriculture nowadays has been an important key of success for many countries in the world including Malaysia. To achieve the status of a developed nation in 2020, Malaysia has rejuvenated its agricultural activities. Contract farming is one of it and can be considered as a new agriculture activity in Malaysia. It has a huge potential to uplift the level of economic and social stratum of people that depend on agriculture as their major source of income. However, this innovative and economic viable farming opportunity demand a strong commitment from our backup generation which is the youth since they are the pillar to the sustainability of agriculture. This study inspects the attitude of Malaysian university students towards contract farming and factors that influence it. Data was collected using a survey questionnaire. The instrument was pre-tested to ensure its reliability and validity. To fulfill the determined objectives, a total of 194 university students from two agriculture based higher institutions were selected. Based on the stepwise regression analysis performed, it can be noted that four factors which are acceptance, perception, support and knowledge are significant predictors of youths’ attitude towards contract farming. This study recommends that specific courses on contract farming should be exposed to university students to develop and strengthen their positive attitude and awareness towards contract farming that would lead them to pursue their career in contract farming once they have graduated.